Preservation of Visual Cortex Plasticity in Retinitis Pigmentosa. (1st January 2020) - Begenisic, Tatjana; Mazziotti, Raffaele; Sagona, Giulia; Lupori, Leonardo; Sale, Alessandro; Galli, Lucia; Baroncelli, Laura
Highlights: Cortical circuits of rd10 mice show physiological levels of plasticity even at advanced stages of retinal degeneration. Synaptic plasticity in the visual cortex is still present when retinal degeneration is complete. Harnessing the plastic potential of the visual cortex could be helpful for therapeutic purposes in RP. Abstract: Retinitis Pigmentosa (RP) is a class of inherited disorders caused by the progressive death of photoreceptors in the retina. RP is still orphan of an effective treatment, with increasing optimism deriving from research aimed at arresting neurodegeneration or replacing light-responsive elements. All these therapeutic strategies rely on the functional integrity of the visual system downstream of photoreceptors. Whereas the inner retinal structure and optic radiation are known to be considerably preserved at least in early stages of RP, very little is known about the visual cortex. Remarkably, it remains completely unclear whether visual cortex plasticity is still present in RP. Using a well-established murine model of RP, the rd10 mouse, we report that visual cortical circuits retain high levels of plasticity, preserving their capability of input-dependent remodelling even at a late stage of retinal degeneration.